Romance & Cigarettes - Turturro, John.; Gandolfini, James; Susan Sarandon; Kate Winslet; Steve Buscemi; Bobby Cannavale; Mandy Moore; MaryLouise Parker; Aida Turturro; Christopher Walken; Barbara Sukowa; Elaine Stritch; et al. (USA United Artists, 2005)
Romance and Cigarettes is a down-and-dirty musical love story set in the world of the working class. Nick (James Gandolfini) is an ironworker who builds and repairs bridges. He's married to Kitty (Susan Sarandon), a dressmaker, a strong and gentle woman with whom he has three daughters. He is carrying on a torrid affair with a redheaded woman named Tula (Kate Winslet). Nick is basically a good, hardworking man driven forward by will and blinded by his urges. Like Oedipus at Colonus, he is sent into exile and searches to find his way back through the damage he has done. In an imaginative, humorous, and touching way, Romance and Cigarettes explores the cost and value of a relationship through life and death. When the characters can no longer express themselves with language, they break into song, lip-synching the tunes lodged in their subconscious. It is their way to escape the harsh reality of their world - to dream, to remember, and to connect to another human being.
Languages: English, Turkish Subtitles: English, Turkish
Keywords: Comedy; Musical; Romance